Crowding and the Furrow Illusion. (September 2018) - Anstis, Stuart; Cavanagh, Patrick
A spot moves vertically across a large grating of oblique parallel lines. When viewed peripherally, the motion path looks oblique, close to the orientation of the background grating. Even when the grating's orientation is concealed by crowding, it can still deflect the spot's perceived motion path.